(untitled) (Studia Prawnicze / The Legal Studies, 1981)
Socio-economic changes observed during the last years and political activisation of the wide ranges of society cause the need for quick development and de- epening of democracy. The key-problems here are participation of the citizens and self-government. According to the Author, classic system of representation with all its typical institutions must undergo radical changes. The Author makes a critical analysis of the classic representation system stressing the weakness of the ties between the representatives and the re- presented and subjecting the representatives (députées) to the élites of power and especially to class leaderships of political parties. The Author comes to the conclusion, that classic system of representation is inadequate to socialist de- mocracy and thus it is necessary to create representation of a new type. Accord- ing to the Author this idea is best realized in the developed delegation system. Pointing out to historical sources of the delegation system the Author pro- ceeds to the analysis of the contents of this institution. He stresses direct - as based on universal elections - relation of the delegates to the citizens and including wide ranges of society to the process of making political decisions. The system of delegations is defined in the constitution of the Socialist Federal Republic of Yougoslavia of 1974. It creates the mechanism of appointing delegations by the working people organized in basic circles of self-government. The delegations - by taking part in socio-political organizations and in their activity - participate also in creating and determining the principles of functioning of the assemblies (“skupsztyna”). In Yougoslavia a wide network of delegations was thus established, representing organizations, self-governed com- munities and socio-political organizations in which a great number of the working people is engaged. The delegations constitute the links of the self-governed basis with the “skupsztyna”, so that every decision finds its foundation in this very basis although its final shape is given by the “skupsztyna”. Undoubtedly, the decision-making process thus shaped gains democratic clearness and self-govern- mental character.